An estrogen (17α-ethinyl estradiol-3-sulfate) reduces mortality in a swine model of multiple injuries and hemorrhagic shock. Issue 1 (January 2022) - Abdou, Hossam; Morrison, Jonathan J.; Edwards, Joseph; Patel, Neerav; Lang, Eric; Richmond, Michael J.; Elansary, Noha; Gopalakrishnan, Mathangi; Berman, Jonathan; Hubbard, William J.; Scalea, Thomas M.; Chaudry, Irshad H.
Abstract : BACKGROUND: Although 17α-ethinyl estradiol-3-sulfate (EES) reduces mortality in animal models of controlled hemorrhage, its role in a clinically relevant injury model is unknown. We assessed the impact of EES in a swine model of multiple injuries and hemorrhage. METHODS: The study was performed under Good Laboratory Practice, with 30 male uncastrated swine (25–50 kg) subjected to tibial fracture, pulmonary contusion, and 30% controlled hemorrhage for an hour. Animals were randomized to one of five EES doses: 0 (control), 0.3, 1, 3, and 5 mg/kg, administered postinjury. Subjects received no resuscitation and were observed for 6 hours or until death. Survival data were analyzed using Cox-proportional hazard regression. Left ventricular pressure-volume loops were used to derive preload recruitable stroke work as a measure of cardiac inotropy. Immediate postinjury preload recruitable stroke work values were compared with values at 1 hour post–drug administration. RESULTS: Six-hour survival for the 0, 0.3, 1, 3, and 5 mg/kg groups was 0%, 50%, 33.3%, 16.7%, and 0%, respectively. Following Cox regression, the hazard (95% confidence interval) of death was significantly reduced in the 0.3 (0.22 [0.05–0.93]) and 1 (0.24 [0.06–0.89]) mg/kg groups but not the 3 (0.49 [0.15–1.64]) and 5 (0.46 [0.14–1.47]) mg/kg groups. Mean survival time was significantly extended in the 1 mg/kg group (246 minutes) versus the 0 mg/kg group (96 minutes) ( p = 0.04, t test). At 1 hour post–drug administration, inotropy was significantly higher than postinjury values in the 0.3 and 1 mg/kg groups ( p = 0.003 and p < 0.001, respectively). Inotropy was unchanged in the 3 and 5 mg/kg groups but significantly depressed in the control ( p = 0.022). CONCLUSION: Administration of EES even in the absence of fluid resuscitation reduces mortality and improves cardiac inotropy in a clinically relevant swine model of multiple injuries and hemorrhage. These findings support the need for a clinical trial in human trauma patients. Abstract : Supplemental digital content is available in the text.